2021
DOI: 10.1021/acsnano.1c06625
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Ligand Selection Affects Stoichiometry, Carrier Dynamics, and Trapping in CuInSe2 Nanocrystals

Abstract: CuInSe2 nanocrystals exhibit tunable near-infrared bandgaps that bolster utility in photovoltaic applications as well as offer potential as substitutes for more toxic Cd- and Pb-based semiconductor compositions. However, they can present a variety of defect states and unusual photophysics. Here, we examine the effects of ligand composition (oleylamine, diphenylphosphine, and tributylphosphine) on carrier dynamics in these materials. Via spectroscopic measurements such as photoluminescence and transient absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 94 publications
(175 reference statements)
0
6
0
Order By: Relevance
“…64 For ternary QDs, Schaller et al examined the effects of ligand composition (OAm, diphenylphosphine, and tributylphosphine) on the band gap of CuInSe 2 QDs, and they found that the band gap can be controlled between 1.27–1.43 eV by using these three ligands. 69…”
Section: Effect Of Surface Ligands On Photocatalysis With Quantum Dotsmentioning
confidence: 99%
See 3 more Smart Citations
“…64 For ternary QDs, Schaller et al examined the effects of ligand composition (OAm, diphenylphosphine, and tributylphosphine) on the band gap of CuInSe 2 QDs, and they found that the band gap can be controlled between 1.27–1.43 eV by using these three ligands. 69…”
Section: Effect Of Surface Ligands On Photocatalysis With Quantum Dotsmentioning
confidence: 99%
“…101 NMR spectroscopy is a convenient non-destructive-tool for determining the structure of ligands, assessing the coverage of ligands, and distinguishing between surface-bound and free ligands. 102,103 A variety of heteroatoms and functional groups in the ligand bound to the surface of the QDs can be detected by 1 H, 13 C and 31 P NMR, including phosphonic acids, 104 phosphines/phosphine oxides, 69,[104][105][106] amines, 69,89,105-107 fatty acids, 64,67,98,[108][109][110] amino acids, 111 carboxylic acids/ carboxylate 90,107,109,[112][113][114] and thiols. [114][115][116] For example, Herman et al reported the structure determination of capped ligands on the surface of CdSe QDs by 31 P and 1 H NMR.…”
Section: Characterization Techniques Of Surface Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…[108] A recent study reported by Harvey et.al in 2021 showed that synthetic ligand selection affected the incorporation of defects within the crystalline lattice and passivation of the surfaces, which led to different stoichiometry, and carrier dynamics, and trapping in CuInSe 2 NCs. [109] Mei et al reported the microwave-assisted synthesis of Cu-In-S/ZnS QDs with dual ligands on their surfaces, and different ratios of thioglycolic acid (TGA) together with sodium citrate (SC) resulted in different shapes and fluorescence intensity of QDs, addressing the importance of ligand in morphology control and performance-boosting during the synthesis process. [44] The length of the ligand also has a significant impact on the performance of the synthesized MCQDs.…”
Section: Surface Ligand Designmentioning
confidence: 99%